PERAN PEREMPUAN TULANG PUNGGUNG KELUARGA : STUDI KASUS PEKERJA PANTI PIJAT MIGRAN DI BATAM - ANA LINDATUS SHOLEHA; YUNITA WULANDARI (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study explores the role of women as the backbone of the family through a case study of massage parlor workers from Karangsemanding Village who migrated to Batam. The primary aim of this research is to understand their social background, life dynamics, and the social impact of their role as the main breadwinners. Using a qualitative approach and in-depth interviews, the study finds that most of these women come from economically disadvantaged families, have low levels of education, and are compelled by financial needs to support their families. In their work at massage parlors, they face social stigma, psychological pressure, and challenges in maintaining relationships with their families back home. Nevertheless, they demonstrate resilience and survival strategies that reflect their central role in sustaining family life. These findings highlight the need for greater attention to the condition of female workers in the informal sector and the importance of more inclusive and humane public policies.